Estimating terpene and terpenoid emissions from conifer oleoresin composition. (July 2015) - Flores, Rosa M.; Doskey, Paul V.
Abstract: The following algorithm, which is based on the thermodynamics of nonelectrolyte partitioning, was developed to predict emission rates of terpenes and terpenoids from specific storage sites in conifers: E i = x o r i γ o r i p i ∘ where E i is the emission rate (μg C gdw −1 h −1 ) and p i ∘ is the vapor pressure (mm Hg) of the pure liquid terpene or terpenoid, respectively, and x o r i and γ o r i are the mole fraction and activity coefficient (on a Raoult's law convention), respectively, of the terpene and terpenoid in the oleoresin. Activity coefficients are calculated with Hansen solubility parameters that account for dispersive, polar, and H-bonding interactions of the solutes with the oleoresin matrix. Estimates of p i ∘ at 25 °C and molar enthalpies of vaporization are made with the SIMPOL.1 method and are used to estimate p i ∘ at environmentally relevant temperatures. Estimated mixing ratios of terpenes and terpenols were comparatively higher above resin-acid- and monoterpene-rich oleoresins, respectively. The results indicated a greater affinity of terpenes and terpenols for the non-functionalized and carboxylic acid containing matrix through dispersive and H-bonding interactions, which are expressed in the emission algorithm by the activity coefficient. The correlation between measured emission rates of terpenes and terpenoids for Pinus strobus and emission rates predicted with the algorithm were very good ( R = 0.95). Standard errors for the range and average of monoterpene emission rates were ±6 – ±86% and ±54%, respectively, and were similar in magnitude to reported standard deviations of monoterpene composition of foliar oils (±38 – ±51% and ±67%, respectively). Highlights: A new terpene and terpenoid emission algorithm for conifers was developed. The algorithm is based on the thermodynamics of nonelectrolyte partitioning. Emission rates are related to conifer oleoresin composition. Activity coefficients account for solute–oleoresin interactions. The emission algorithm is a promising approach for developing emission inventories.